STUDENTS’ PERCEPTION TOWARDS THE IMPLEMENTATION OF TALKING STICK MODEL TO PRACTICE ENGLISH SPEAKING SKILL - Syahyuri; Riyanto (Department of English Education, Universitas Panca Sakti Bekasi, 2019)
This research aimed to find out the students’ perception on the implementation of Talking Stick model to practice speaking skill, whether it is positive or negative. Since English is considered as a foreign language in Indonesia, so it is very important to practice the students’ speaking skill to communicate effectively. The English teacher however, can use the learning model as the classroom activity to motivate and engage the students to be confident to speak in front of the class. There many learning model, one of them is Talking Stick model. This learning model gives more opportunity to the students to speak in front of the class by using Talking Stick. The researcher formulated two questions. The researcher employed a survey model. There are two research instruments in this research which are questionnaire and interview.